2018
DOI: 10.1177/1354066118780996
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the poverty of Western historical imagination: Alternative analogies for making sense of the South China Sea conflict

Abstract: This article analyzes the use of historical analogies to interpret and explain foreign policy behavior, focusing on the South China Sea conflict. In reviewing coverage in the international English-language press, we find a range of historical analogies, from the conflict between Athens and Sparta to the 1938 Munich agreement, to interpret China’s strategy and motivations in the region. While analogies are powerful tools for interpreting international events, their use has dangers as they are often deployed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Thirdly, the American media reflects political issues towards the BRI project, and the European media reflects economic issues. Previous authors have observed similar patterns due to different logics (Kopper and Peragovics, 2019). For instance, Chinese logic differs from the audience, and the audience logics differs from each other in the context of the BRI project (Liu et al, 2018;No ¨lke et al, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…Thirdly, the American media reflects political issues towards the BRI project, and the European media reflects economic issues. Previous authors have observed similar patterns due to different logics (Kopper and Peragovics, 2019). For instance, Chinese logic differs from the audience, and the audience logics differs from each other in the context of the BRI project (Liu et al, 2018;No ¨lke et al, 2015).…”
Section: Discussionmentioning
confidence: 81%
“…Thomas ( 2004 ) argues that when major IR journals study the "Third World," they analyze it as a security threat. The argument that scholars ignore the non-Western world is related to concerns that the dominant voices in IR theorizing tend to be scholars in Western countries ( Tickner 2003 ;Zhang 2003 ;Bilgin 2008 ;Acharya and Buzan 2010 ;Gleditsch et al 2014 ;Deciancio 2016 ;Kopper and Peragovics 2019 ). Interestingly, one recent study of five prominent IR journals found that there do not seem to be regional differences in coverage, although it did find that the United States receives more scholarly attention than other countries ( Hendrix and Vreede 2019 ).…”
Section: The Western Bias Explanationmentioning
confidence: 99%
“…This appears to have occurred with other subjects, such as research on climate change's effects ( Hendrix 2017 ;Adams et al 2018 ). In conflict research, scholars have asserted that over-focus on Western cases has affected conclusions on topics such as military innovation ( Sharman 2018 ) and Chinese security strategy ( Kopper and Peragovics 2019 ). Beyond these specific subjects, it is unclear if similar biases are present broadly in conflict studies.…”
Section: Introductionmentioning
confidence: 99%